Manajemen Peserta Didik dalam Meningkatkan Prestasi Belajar di SDN Babatan 1 - Wulandari, Retno Innesh; Setianingsih, Aida Yuniati; Maharani, Dian Kusuma; Zamzami, Ma’in; Ramadhani, Adinda Dwi; Wulandari, Ayu; Nuphanudin, Nuphanudin (MASALIQ, 2024)
The purpose of this research is to find out how to improve students' academic achievement in educational institutions. This research uses several types of methods, namely quantitative description methods and literature review systems. The results of this study indicate that there are 373 students in grades 1 to 6, where the learning uses 2 types of curriculum, namely K-13 and Merdeka Curriculum. Furthermore, the results show that the way or steps of SDN Babatan 1 in improving learning achievement is through management or by managing students, this can be realized by implementing extracurricular activities and implementing discipline which aims to create an outstanding and competitive generation so that it is useful in the future. The implementation of extracurricular activities and the application of discipline organized at SDN Babatan 1 are also expected to help broaden the knowledge of students and even foster the interests and talents of students. In addition to the efforts made by SDN Babatan 1 above, efforts that can be made to improve students' learning achievement are the role of educators who must participate in encouraging students to be motivated by the experiences provided by educators. This is because in the process of success of a learner cannot be separated from the influence of the quality of human resources.